Analisis Penggunaan Algoritma Pemrograman dan Aplikasi Geogebra dalam Pembelajaran Matematika Geometri - Muhammad Farhan; Yahfizham Yahfizham (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
Mathematics is an important component of education. Geometry is a branch of mathematics that focuses on abstract objects that are often encountered in everyday life. Two-dimensional geometry (flat shapes) and three-dimensional geometry (spatial shapes) discuss abstract forms of real objects. In today's digital era, humans cannot be separated from utilizing technology, including teachers and even the Ministry of National Education continues to support the use of technology in learning. GeoGebra is a very useful math learning tool that allows students to understand abstract math concepts visually and easily understood. This research was conducted to evaluate how the use of programming algorithms and GeoGebra applications can improve the learning of mathematical geometry. This study was conducted to evaluate how the use of programming algorithms and GeoGebra applications can improve geometry math learning. The method used is SLR (Systematic Literature Review). The results of the study are the use of programming algorithms and GeoGebra applications in learning mathematical geometry has a positive impact on the functionality and capabilities of this application in the context of learning geometry.